2019
DOI: 10.1136/tobaccocontrol-2019-055193
|View full text |Cite
|
Sign up to set email alerts
|

What factors reliably predict electronic cigarette nicotine delivery?

Abstract: BackgroundThe ability of an electronic cigarette (e-cigarette) to deliver nicotine effectively may be dependent on features of the device, the liquid and the user. Some of these features have been examined in previous work (eg, liquid nicotine concentration and puff topography), while others have not (eg, nicotine dependence and demographic characteristics). The purpose of this secondary analysis is to examine such features as predictors of e-cigarette nicotine delivery using a relatively large sample.MethodsF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…Thus, for higher wattage devices (ie, 40.5-45 W), paired with 3-8 mg/ml nicotine, puff duration may affect nicotine delivery, as others have noted. 14,15 However, the puff duration observed in this study was similar to other studies on ENDS-naïve cigarette smokers. 8 Differences in puff duration do not fully explain all differences in nicotine delivery.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, for higher wattage devices (ie, 40.5-45 W), paired with 3-8 mg/ml nicotine, puff duration may affect nicotine delivery, as others have noted. 14,15 However, the puff duration observed in this study was similar to other studies on ENDS-naïve cigarette smokers. 8 Differences in puff duration do not fully explain all differences in nicotine delivery.…”
Section: Discussionsupporting
confidence: 89%
“…Prior research has shown puff duration influences nicotine delivery. 40 For the seven machine testing studies reviewed here, puff volume explained 37% of the variability in nicotine measured per puff. The puff topography study was of ad libitum use over 60 min, while the PK studies provided participants 4.5-10 min to use JUUL, followed by a period of abstinence.…”
Section: Discussionmentioning
confidence: 96%
“…Since puffing topography is an indirect method of determining exposure to smoke or vapour, the higher puff volumes and more frequent puffs observed in e-cigarette and waterpipe user could potentially increase the exposure to toxicants. 33 …”
Section: Comparison Of Smoking/vaping Patterns For Tobacco Cigarettementioning
confidence: 99%